Comparative Analysis of the Antiviral Effects Mediated by Type I and III Interferons in Hepatitis B Virus–Infected Hepatocytes. (29th March 2019) - Bockmann, Jan-Hendrik; Stadler, Daniela; Xia, Yuchen; Ko, Chunkyu; Wettengel, Jochen M; Schulze zur Wiesch, Julian; Dandri, Maura; Protzer, Ulrike
Abstract: Background: Type III interferons (IFNs) (λ1–3) activate similar signaling cascades as type I IFNs (α and β) via different receptors. Since IFN-α and lymphotoxin-β activate cytosine deamination and subsequent purging of nuclear hepatitis B virus (HBV) DNA, we investigated whether IFN-β and -λ may also induce these antiviral effects in differentiated HBV-infected hepatocytes. Methods: After determining the biological activity of IFN-α2, -β1, -λ1, and -λ2 in differentiated hepatocytes, their antiviral effects were analyzed in HBV-infected primary human hepatocytes and HepaRG cells. Results: Type I and III IFNs reduced nuclear open-circle DNA and covalently closed circular DNA (cccDNA) levels in HBV-infected cells. IFN-β and -λ were at least as efficient as IFN-α. Differential DNA-denaturing polymerase chain reaction and sequencing analysis revealed G-to-A sequence alterations of HBV cccDNA in IFN-α, -β, and -λ–treated liver cells indicating deamination. All IFNs induced apolipoprotein B messenger RNA–editing enzyme–catalytic polypeptide-like (APOBEC) deaminases 3A and 3G within 24 hours of treatment, but IFN-β and -λ induced longer-lasting expression of APOBEC deaminases in comparison to IFN-α. Conclusions: IFN-β, IFN-λ1, and IFN-λ2 induce cccDNA deamination and degradation at least as efficiently as IFN-α, indicating that these antiviral cytokines are interesting candidates for the design of new therapeutic strategies aiming at cccDNA reduction and HBV cure. Abstract : Similar to interferon-α, interferon-β and -λ can purge the hepatitis B virus persistence form, cccDNA, from infected hepatocytes and control virus replication without killing the cells. All interferons induce cytosine deamination of cccDNA, with interferon-α showing the least favorable kinetics.